2012
DOI: 10.1007/978-3-0348-0525-4_2
|View full text |Cite
|
Sign up to set email alerts
|

O2 Analysis on a Fluorescence Spectrometer or Plate Reader

Abstract: In this chapter, the use of Pt-porphyrin-based extracellular and intracellular O 2 sensing probes (ecO 2 and icO 2 ) on a TR-F plate reader format is described and critically assessed. The principles underpinning extracellular measurement are outlined and the assessment of biological oxygen consumption in prokaryotic cells, eukaryotic cells and small organisms is outlined along with a description of how such measurements can contribute to the development of a detailed picture of cell metabolism. The use of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…From the data in Table 2 , the following conclusions can be drawn: For the MitoXpress probe, basal intensity signals in the RCC and MLS media (highlighted in red) were strongly quenched, dropping below the acceptable levels (>30 k cps) for this type of instrument and assay [ 27 ]. On the other hand, its maximal Int signals remained high and easy to measure in all of the media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the data in Table 2 , the following conclusions can be drawn: For the MitoXpress probe, basal intensity signals in the RCC and MLS media (highlighted in red) were strongly quenched, dropping below the acceptable levels (>30 k cps) for this type of instrument and assay [ 27 ]. On the other hand, its maximal Int signals remained high and easy to measure in all of the media.…”
Section: Resultsmentioning
confidence: 99%
“…In MMG, baseline and maximal Int signals of all of the probes are reduced 3–6 fold. For PtPEG 4 , baseline Int signals dropped below the acceptable threshold for respirometry (>30 k cps) [ 26 , 27 ]. Only the NanO2 probe showed close-to-normal sigmoidal profiles of Int and LT signals, but its LT baseline reduced to 15 µs and maximal LT down to 30 µs ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…For this family of probes, toxicity effects were studied with cell and spheroid models (Dmitriev et al, 2012; Fercher et al, 2011, 2012; Zhdanov et al, 2012), and shown to become significant at probe concentrations >50 µg/ml and loading times >16h. Here we applied higher concentrations (10 mg/ml) but in a small volume and short loading times (0.5–1h) and the morphological and functional examination of brain tissue samples showed no signs of toxicity (see the results).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its role as a transcription factor involved in the regulation of the expression of lysosomal genes, STAT3 has been shown to regulate intracellular pH. Liu et al [100] showed that under conditions in which the intraluminal pH of the lysosomes is neutralized, leading to the acidification of the cytosolic pH (for example, by inhibiting the V-ATPase (Bafilomycin A or Concanamycin) [101][102][103][104] or by directly sequestering H + in the lysosomal compartment (e.g. chloroquine) [105]; or through the acidification of the cytosolic pH, for example, by using inhibitors of the Na + /H + exchanger (i.e., EIPA or cariporide) [106]), STAT3 shows a punctate pattern by specifically interacting with the lysosomal V-ATPase complex.…”
Section: Stat Family: Regulating Lysosomes From Cell Death To Homeost...mentioning
confidence: 99%